Nonlinear Static vs. Incremental Dynamic Analysis of Infilled Frames with Open First Floor - Todorov, Koce; Lazarov, Ljupco (Society for materials and structures testing of Serbia, 2018)
Masonry infill, as a part of building structures, is characterised with significant in plane strength and stiffness and it can greatly alter the response of structures exposed to seismic loads. Irregular distribution of infill in plane and along building height can lead to series of unfavourable effects (torsion effects, dangerous collapse mechanisms, soft or weak storey, variations in the vibration period, etc.). In order to investigate the influence of irregular distribution of masonry infill to the seismic performance of code designed reinforced concrete frames, an extensive nonlinear static and dynamic analysis was performed. Six reinforced concrete frames with different number of storeys, designed as bare frames were analysed. In the phase of assessment, all structures were upgraded with the masonry infill panels in all storeys except the first one. Masonry infill was defined with two different strength and stiffness characteristics. The obtained results show significant influence of masonry infill on the main structural characteristics: strength, stiffness and ductility, as well as on the seismic performance of analysed frames.
Keywords: nonlinear static, incremental dynamic; masonry infill; open ground floor